MP29: Using the Calgary audit and feedback framework to get the most out of physician practice reports. (May 2020) - Dowling, S.; Peterson, A.; Wong, C.; Cooke, L.; Bond, C.
Abstract : Innovation Concept: The Calgary Audit and Feedback Framework (CAFF) is an innovative tool developed by the Physician Learning Program (PLP). By addressing four key factors –relationships, question choice, data visualization, and facilitation – CAFF addresses common barriers to physicians receiving their practice data. The goal of this study is to assess whether CAFF-facilitated physician performance improvement (PPI) sessions: 1) improve physicians' receptiveness to their practice data, and 2) encourage physicians to both identify opportunities for practice change and create action plans. Methods: Peer facilitators were trained to facilitate PPI sessions using the CAFF model. In Calgary, 51/180 emergency physicians have attended at least one of the six PPI sessions. The sessions were evaluated using surveys, commitment to change forms, and the Feedback Orientation Scale (FOS). The FOS is a scale developed to measure a participant's orientation to performance feedback across the four domains of utility, accountability, social awareness, and feedback self-efficacy. Curriculum, Tool, or Material: The PLP has developed and implemented CAFF as a framework to help foster socially constructed learning in audit and group feedback sessions. The CAFF model ensures that the aforementioned four key factors are considered for design and implementation of audit and group feedback. The PLP found that establishing the meaning and credibility of the data is a necessary precursor to reflection and action planning. Conclusion: The FOS was completed for 25/32 physicians. The mean FOS score improved by 0.339 (p < 0.001; z=−3.863). While the mean scores all four domains increased, 'Feedback Self-Efficacy' increased the most by .0620 (p < 0.001; z=−3.999). Participants reported that examples of changes made by the peer facilitators were particularly helpful. Evaluations from the sessions suggested physicians overwhelmingly agreed or strongly agreed that the peer comparison was valuable, that the reports helped them reflect on their practice, and that the session helped them identify learning opportunities and strategies to change their practice.